Comparison of Income Statement Approach and Shari'ate Value Added Statement Approach in Assessing the Financial Performance of Islamic Banks in Indonesia - agus faisal (Global Review of Islamic Economics and Business, 2016)
The purpose of this study is to comparison in financia performance of Islamic banks in Indonesia by using the Income Statement (IS) approach and Shari'ate Value Added Statement (SVAS) approach. The type of research is quantitative, sample using a purposive sampling technique with the criteria of Islamic banks in Indonesia the which presents a financial annual report the period 2008-2012. Financial ratios used consisted of Return On Asset (ROA), Return on Equity (ROE), the ratio between the total net income by total productive assets (LBAP), Net profite Margin (NPM), and Operating Expense to Operation Income (OEOI), Analysis tool used to prove the hypothesis of this study is an independent sample t-test and Mann Whitney U. The result Showed that the average financial ratios (ROA, ROE, LBAP, NPM and OEOI) there are differences singnificant between the model of  IS and SVAS. Differences in the ratio of financial performance is due to the differences in the design of the presentation and disclosures relating to profit and added value. Income Statement "IS" looked at  income as profit, whereas the Shari'ate Value Added Statement "SVAS" looked at income as an added value.